2007
DOI: 10.1111/j.1600-051x.2007.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in periodontal health among 35‐year‐olds in Oslo, 1973–2003

Abstract: The results suggest that periodontal health and oral hygiene have been improving among 35-year-olds in Oslo during the last 30 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
63
5
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 22 publications
8
63
5
2
Order By: Relevance
“…The main result of the present study was that the prevalence of ABL has decreased over the past 30 years, as reported in other studies (5,6). However, an increase in moderate ABL and visible calculus on radiographs was seen between the study years 2008 and 2013.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The main result of the present study was that the prevalence of ABL has decreased over the past 30 years, as reported in other studies (5,6). However, an increase in moderate ABL and visible calculus on radiographs was seen between the study years 2008 and 2013.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence varies between countries, but together with dental caries and its sequelae, periodontitis is the most common reason for tooth loss in adults (1)(2)(3)(4). The vast majority of studies reveal that the prevalence of periodontally healthy individuals is increasing (5)(6)(7). Severe periodontitis is more common in older age groups, with a prevalence of 5% to 15% in most populations (8).…”
Section: Introductionmentioning
confidence: 99%
“…Eleven percent had CPITN scores of 4 (at least one pocket > or = 6 mm). A study on periodontal health status of 35 year olds in Oslo showed a decrease in the proportion of persons with CPITN scores of 4 from 21.9% in 1984 to 8.1% in 2003 [25]. It is difficult to compare the DMFT and CPITN values from this study with the studies from Oslo and Trøndelag because of the small sample size and wide age range in this study.…”
Section: Discussioncontrasting
confidence: 43%
“…It is one of the most prevalent infectious diseases in the world. With percentages of moderate disease ranging from just below 20% in an age group of 30 to 40 year-olds in Swedish and Norwegian studies to even up to 38% of severe cases in the United States in an on average 75 year-old male population [1-3]. Besides high prevalence also links to systemic diseases have been described.…”
Section: Introductionmentioning
confidence: 99%